High-Risk Opioid Prescribing Trends: Prescription Drug Monitoring Program Data From 2010 to 2018. Issue 4 (9th July 2021) - Ball, Sarah J.; Simpson, Kit; Zhang, Jingwen; Marsden, Justin; Heidari, Khosrow; Moran, William P.; Mauldin, Patrick D.; McCauley, Jenna L.
Abstract : Objective: Deaths due to opioids have continued to increase in South Carolina, with 816 opioid-involved overdose deaths reported in 2018, a 9% increase from the prior year. The objective of the current study is to examine longitudinal trends (quarter [Q] 1 2010 through Q4 2018) of opioid prescribing volume and high-risk opioid prescribing behaviors in South Carolina using comprehensive dispensing data available in the South Carolina Prescription Drug Monitoring Program (SC PDMP). Design: Retrospective analyses of SC PDMP data were performed using general linear models to assess quarterly time trends and change in rate of each outcome Q1 2010 through Q4 2018. Participants: Opioid analgesic prescription fills from SC state residents between Q1 2010 and Q4 2018. Main Outcome Measures: High-risk prescribing behaviors included (1) opioid prescribing rate; (2) percentage of patients receiving opioids dispensed 90 or more average morphine milligram equivalents daily; (3) percentage of opioid prescribed days with overlapping opioid and benzodiazepine prescriptions; (4) rate per 100 000 residents of multiple provider episodes; and (5) percentage of patients prescribed extended release opioids who were opioid naive. Results: A total of 33 027 461 opioid prescriptions were filled by SC state residents within the time period of Q1 2010 through Q4 2018. A 41% decrease in the quarterly prescribing rate of opioids occurred from Q1 2010 to Q4 2018. The decrease in overall opioid prescribing was mirrored by significant decreases in all 4 high-risk prescribing behaviors. Conclusion: PDMPs may represent the most complete data regarding the dispensing of opioid prescriptions and as such be valuable tools to inform and monitor the supply of licit opioids. Our results indicate that public health policy, legislative action, and multiple clinical interventions aimed at reducing high rates of opioid prescribing across the health care ecosystem appear to be succeeding in the state of South Carolina.